The chinese surveillance system of covid-19 disease in the light of artificial intelligence - Nagy, Kitti; Boštíková, Vanda (Vojenské zdravotnické listy, 2024)
There are two key sources of data that contribute to biomedicine research: surveillance and questionnaires and interviews. The Centers for Disease Control and Prevention (CDC, Atlanta, GA, USA) defines surveillance as the ongoing systematic collection, analysis, and interpretation of health data, essential to the planning, implementation, and evaluation of public health practice, closely integrated with the timely dissemination to those who need to know. The three things to keep in mind about surveillance systems are that they are ongoing (collecting information only once is not a surveillance system), the data collected are used (analyzed and interpreted) and finally, surveillance data is disseminated. There are several tangible applications of surveillance as a tool. For example, surveillance data can be used to establish public health priorities, aid in determining resource allocation and assess or evaluate public health programs. Surveillance data originate from many sources; therefore, standardization of surveillance practices is an ongoing challenge.For epidemiologists specifically, surveillance data can be used to determine a baseline for the detection of epidemics or for early detection of epidemics. This is clearly the positive meaning and impact of this system collecting sensitive population data. However, expression surveillance means in effect, supervision or control. The subsequent resulting regulations are the subject of reflection in this article.
Keywords: paternalismus; vědecká epidemiologie; Paternalism; Medical Informatics; lékařská informatika; China; lidé; Government; umělá inteligence; epidemiologické monitorování; Legal Epidemiology; vláda; Artificial Intelligence; COVID-19; Epidemiological Monitoring; Čína; Humans